2021
DOI: 10.3390/membranes11110845
|View full text |Cite
|
Sign up to set email alerts
|

Removal and Fouling Influence of Microplastics in Fertilizer Driven Forward Osmosis for Wastewater Reclamation

Abstract: Insufficient removal of microplastics (MPs) and nanoplastics (NPs) may exert negative effects on the environment and human health during wastewater reclamation. The fertilizer-driven forward osmosis (FDFO) is an emerging potential technology to generate high-quality water for irrigation of hydroponic systems. In this study, the removal of MPs/NPs by the FDFO process together with their impact on FDFO membrane fouling was investigated, due to FDFO’s low molecular weight cut-off and energy requirement by using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…In recent studies, fertilizers with different osmotic pressures were selected as DS to achieve the purpose of high-quality water recovery from synthetic wastewater (containing microplastics and nanoplastics) [1], domestic wastewater [128], local municipal wastewater [128], synthetic brackish water [146], and raw sewage [177]. However, most of the reported water flux was relatively low using CTA membrane due to solute build-up in the final FS which was mainly attributed to reverse nutrient (K + , NH + 4 , and PO 3− 4 ) fluxes.…”
Section: From An Agricultural Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, fertilizers with different osmotic pressures were selected as DS to achieve the purpose of high-quality water recovery from synthetic wastewater (containing microplastics and nanoplastics) [1], domestic wastewater [128], local municipal wastewater [128], synthetic brackish water [146], and raw sewage [177]. However, most of the reported water flux was relatively low using CTA membrane due to solute build-up in the final FS which was mainly attributed to reverse nutrient (K + , NH + 4 , and PO 3− 4 ) fluxes.…”
Section: From An Agricultural Perspectivementioning
confidence: 99%
“…In past decades, freshwater demand has risen substantially owing to population growth, economic development, and different consumption patterns [1]. This ultimately, induced a global clean water scarcity and this scenario will only get worse in the next few decades.…”
Section: Introductionmentioning
confidence: 99%
“…The wind transfer is credited with creating 7% of all ocean contamination (Chen et al 2020 ). There may also be sources of AMPs, such as plastic fragments released from clothing and house furnishings, materials in buildings, waste incineration, landfills, industrial emissions, particle resuspension, particles from traffic, synthetic particles used in horticultural soils (e.g., polystyrene peat), sewage sludge used as fertiliser, and tumble dryer exhaust (Prata 2018 ; Wang et al 2021a , b , c ). Fashion and season play a significant role in influencing the amount and quality of MPs particles in airborne clothing.…”
Section: Microplastics In the Airbornementioning
confidence: 99%
“…The MPs can absorb persistent organic pollutants (such as polychlorinated biphenyls) (Wang et al 2021a , b , c ) as well as heavy metals (Mao et al 2020 ). A million times more persistent organic pollutants can adhere to plastics than to ambient air, which can further be desorbed by organisms, causing them to accumulate at higher trophic levels (Bakir et al 2014 ) ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane separation processes were proposed in several different treatment schemes for the reuse of water and valuable by-products from wastewater. In this context, Wang et al [ 2 ] evaluated the feasibility of a forward osmosis system to reclaim water for irrigation purposes from wastewater containing nano- and microplastic particles. They found that in the presence of nano- (0.1 μm) and micro (1 μm)-plastic particles, the hydraulic resistance of the fouling layer decreased compared with the control experiments when no particles were present.…”
mentioning
confidence: 99%